Imaging Diagnostics, Biomarkers, and Emerging Trends in Orthopedic Research and Treatment - Gabriela Oliwia Trestka; Wiktoria Domino; Urszula Zelik; Maria Przygoda; Joanna Śnieżna; Kamila Stępień; Sabina Adamczyk; Wojciech Florczak; Jagienka Włodyka; Jakub Dziewic; Karol Dzwonnik (Quality in Sport)
With an aging population, increasing sports participation, and a rising number of obese individuals, researchers are addressing the growing prevalence of musculoskeletal diseases. Early diagnosis is crucial for effective treatment and disease prevention. Imaging techniques and biomarkers are essential tools in orthopedic diagnostics, providing critical insights into disease progression, treatment efficacy, and clinical outcomes prediction.